Magnetic Molecularly Imprinted Polymers: Synthesis and Applications in the Selective Extraction of Antibiotics - Li, Junyu; Wang, Yiran; Yu, Xiuxia (Frontiers in Chemistry, 2021)
Recently, magnetic molecularly imprinted polymers (MMIPs) have integrated molecular imprinting technology (MIT) and magnetic separation technology, and finally become a novel material with specific recognition and effective separation of target molecules. Based on their special function, they can be widely used to detect biomacromolecules and contaminants such as antibiotics. The antibiotic residues in environment not only cause harm to the balance of the ecosystem, but also induce bacterial resistance to specific antibiotics. In view of the above consideration, it is especially important to develop sensitive and selective methods for the measurement of antibiotics in the complex matrix. The combination of MMIPs and conventional analytical methods provide a rapid approach to separate and determine antibiotics residues. This article gives a systematic overview about synthetic approaches of the novel MMIPs materials, briefly introduces their use in sample pretreatment prior to antibiotic detection, and provides a perspective for future research.